An approach to study vibration in stochastic systems based on the asymptotic method - Khiem, Nguyen Tien (Vietnam Journal of Mechanics, 2007)
The well known Fokker-Plank-Kolmogorov Equation Method has been developed to study random vibration in systems with hysteresis that often described by the stochastic integro-differential equations or differential equations with delay.